Involuntary Movements in Cobalamin Deficiency - Özyürek, Hamit; Ince, Hulya; Tasdemir, Haydar Ali; Aydin, Omer Faruk (Klinische Pädiatrie, 2023)
Objective Neurologic problems are frequently described in infants with nutritional vitamin B12 (cobalamin) deficiency.Major neurologic consequences of infantile cobalamin deficiency include delays or regression in neurodevelopment and the occurrence of involuntary movementsMethods We reviewed the medical records of infants with cobalamin deficiency and divided infants with involuntary movements into two groups as those, who developed involuntary movements during vitamin B12 supplementation (Group I) and those, who developed involuntary movements prior to supplementation therapy (Group II).Results We evaluated a total of 32 infants with the diagnosis of cobalamin deficiency. Involuntary movements were observed in 12 out of 32 infants. Group I and Group II consisted of 6 infants each. Of the infants with involuntary movements, five were exclusively breastfed until the time of diagnosis. The majority of infants in Group II had choreoathetoid movements; twitching and myoclonus in the face, tongue, and lips, and tremor in the upper extremities. These involuntary movements disappeared in one to three weeks after clonazepam therapy. In Group I; shaking movements, myoclonus, tremor, and twitching or protrusion were observed in patients’ hands, feet, tongue, and lips on the 3rd-5th day of cobalamin supplementation. These involuntary movements disappeared within 5–12 days of clonazepam therapy.Conclusion Recognition of nutritional cobalamin deficiency is important to perform a differential diagnosis of the condition from seizures or other causes of involuntary movements and avoid aggressive therapy and over treatment.
Keywords: involuntary movement; treatment; cobalamin; infancy